Gender Discourses in Positioning Indonesian Female Migrant Workers - Wening Udasmoro; Setiadi Setiadi (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Indonesian female migrant workers are a group that has over time experienced physical, psychological, and verbal violence in their jobs in foreign countries. The story presented of the struggles of this subordinated group of women remains one-sided and incomplete. The untold part of the story are the experiences they have encountered domestically from within their own country, Indonesia. This article argues that the subordinated position of Indonesian female migrant workers is initially created and strongly reinforced through the discrimination they face within specific social settings in the Indonesian context. One such social setting is at Indonesian international airports. Indonesian international airports are where the female migrant workers are positioned as “others”; rules put in place and their enforcement by airport officials and other passengers show the exclusion of female migrant workers from Indonesian society. Such positioning is an act of discrimination, exploitation, and exercise of power. This study examines what discourses are used in positioning these Indonesian female migrant workers in Soekarno Hatta International Airport, Jakarta. The authors argue, using research data and gender theories, that the positioning of Indonesian female migrant workers is a discursive act. It is committed by various individuals, particularly those (in the power system) that have the position of “we” and “us”, to preserve the social classes, which have become normalized throughout Indonesian history. The research found that the discrimination against female migrant workers is strongly connected to their social class. Although they have financial capital, their position is considered lower than other people in the airport, which creates multiple forms of discrimination, from material to symbolic discrimination and stereotypes.